(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to examine the relationship between electric potential difference and electric current in a conductor with resistance and aims to describe the MPA relationship in adding to the scientific body of physics. The type of research used in this study is quantitative experiment, namely research by conducting practice on ohm’s law physics. The data in this study were obtained from experiments, questions and answers, and documentation. Based on the experimental results shown by the graph, it proves that the potential difference and electric current strength have a significant relationship, which is in accordance with the theory of Ohm’s law. Based on the discussion above, it can be concluded that there is a link or relationship between MPA and the scientific treasures of physics because MPA can add new experiences, understand new theories and so on. From the results of the graphs shown, it can be concluded that the experiments were carried out in accordance with Ohm’s law theory, namely the voltage is directly proportional to the current strength. Therefore, it is necessary to have a practicum guidebook that can train the science of ohm’s law physics